L’étude de l'exégèse coranique dans deux institutions d'enseignement à Fès - Géraldine Jenvrin (Revue des Mondes Musulmans et de la Méditerranée)
This article questions from a comparative perspective, the pedagogy and content of Qur’anic teachings within two institutions in Fez – the old Mosque-University of al-Qarawiyyine on the one hand, and on the other hand, university departments for Islamic Studies (dirāsāt islāmiyya) and Islamic Law (sharīʿa) – and how these sectors reflect an official doctrine which advocates at the same time “modernization” and reform, and a traditionalist Islam focused on legal aspects. Our study is particularly interested in the portrait of a teacher in a cross-over setting, who practices in both types of institution in the city.